Manifestasi Nusantara Mengkini pada Konsep Karya Interior Arsitektur Andy Rahman (Studi Kasus: Omah Boto) - Andreas Ricko Wijaya; Yusita Kusumarini; Filipus Priyo Suprobo (Intra, 2019)
Andy Rahman is an architect who was later known through his work process which tended to uphold and prioritize the elements of Nusantara. When viewed through the development of his work, there are significant differences in his latest work, Omah Boto, which totally works through the exploration of local potential and traditional elements and essences - which are often ignored and abandoned by most designers. This research was conducted to find out the application of the ancestral traditions applied by Andy Rahman and the study of the concept of Andy Rahman who tried to re-establish the tradition to make it appear more up-to-date, modern and contemporary in his work Omah Boto. Using descriptive qualitative methods, namely in-depth interviews with speakers, observations (through seminars and work critics at Omah Boto Open House), documentation of the location and atmosphere of Omah Boto's architectural interiors, as well as literature studies related to Interior and Archipelago Architecture. The results of this study will reveal the extent to which traditional essence applied is implemented in Andy Rahman's architectural interior works in his work Omah Boto.